Including excluded groups: The slow racial transformation of the South African university system - Helena Barnard; Robin A. Cowan; Alan P. Kirman; Moritz Müller (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
This paper looks at the inclusion of excluded groups, notably the racial transformation of the South African university system. Both demand-side factors - are qualified black people hired as faculty? - and supply-side factors - are there enough qualified black people who can be hired as faculty? | need to be aligned. Prior evidence suggests that demand and supply both have both a psychological and a structural dimension. Affrmative action-type regulations address the structural dimension of demand, but homophily (a "love for the own") can nonetheless limit the hiring of faculty in white-dominated hiring committees. On the supply side, the weak education system limits the structural supply of quality black potential academics. But the limited hiring of black academics and resulting limited role models mean that few black people even consider an academic career. This paper presents a model of hiring (either randomly or on a homophilic basis), calibrated with data from the South African university system from the end of Apartheid. Our evidence suggests that even a relatively small reduction of homophily increases the rate at which the excluded group enters the workforce, and also that the effects of homophily and feedback from previous hires are of a similar magnitude. Nonetheless, the conclusions from the model suggest that the relatively long duration of a research career and slow growth of the national university system will result in a slow process of racial transformation.
urn:nbn:de:swb:90-554267
Keywords: O15; O30; I2; 330; universities; racial transformation; South Africa; transformation; higher education access; segregation